2019
DOI: 10.1002/cncy.22149
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical validation studies in effusion cytology: A cautionary tale

Abstract: Precision medicine is driving the increased reliance of biomarker testing by immunohistochemistry (IHC) on cytological specimens. Although the original focus of IHC was to identify a target protein or analyte and deliver nominal results as a positive or negative signal, 1 it has now been expanded to include ordinal results in the form of scoring scales (eg, human epidermal growth factor receptor 2 [HER2] in breast cancer) or predefined positivity cutoffs (eg, a programmed death ligand 1 [PD-L1] assay). 2 The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A relatively frequent use of immunostains in body fluid cytology is the performance of predictive marker studies. Such studies can be reliably performed in malignant cells from effusions if the immunostains are thoroughly validated and the appropriate caveats regarding their use are kept in mind . In this study, we found a relative frequent use of estrogen and progesterone receptor (ER/PR) and Her2 stains for metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 82%
“…A relatively frequent use of immunostains in body fluid cytology is the performance of predictive marker studies. Such studies can be reliably performed in malignant cells from effusions if the immunostains are thoroughly validated and the appropriate caveats regarding their use are kept in mind . In this study, we found a relative frequent use of estrogen and progesterone receptor (ER/PR) and Her2 stains for metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Thoracentesis is a less invasive technique generally performed earlier than tissue biopsy 26 . However, cytologic diagnosis of mesothelioma can be challenging 27 . Cytomorphology is the fundamental basis for a diagnosis of mesothelioma based on cytology, but cytomorphologic features of mesothelioma cells may be observed in the reactive proliferation of mesothelial cells 26,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…26 However, cytologic diagnosis of mesothelioma can be challenging. 27 Cytomorphology is the fundamental basis for a diagnosis of mesothelioma based on cytology, but cytomorphologic features of mesothelioma cells may be observed in the Cancer Cytopathology July 2021 reactive proliferation of mesothelial cells. 26,28,29 In addition, identification of tumor cell invasion of surrounding tissues-the gold standard for diagnosis of MPM 4 cannot be achieved by cytologic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from analytical problems, preanalytical factors such as the frequent use of non-formalin fixatives with cytology samples pose challenges with IHC testing [32]. Technical validation of a satisfactory test performance is therefore required at the level of each laboratory [33].…”
Section: Discussionmentioning
confidence: 99%